2019
DOI: 10.18203/2320-1770.ijrcog20196007
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in obstetrics: a five-year study in a tertiary centre

Abstract: Background: Pregnancy Related Acute Kidney Injury (PRAKI) is a major cause of maternal and foetal morbidity and mortality in developing countries. The incidence has declined due to improvements in reproductive health but it is still associated with significant perinatal mortality and maternal morbidity. It may be due to decrease in renal perfusion or ischemic tubular necrosis from a variety of conditions encountered during pregnancy. Our study aims at determining the predisposing factors and causes of AKI duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Most of the patients in our study were multipara (49.3%) and in stage III AKI 53.0% were multipara, other authors reported PRAKI more common in multipara 62%,[ 11 ] 61.1%,[ 12 ] and 79.6%[ 13 ] respectively, while two studies reported PRAKI more common in primipara (52%). [ 14 15 ]…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Most of the patients in our study were multipara (49.3%) and in stage III AKI 53.0% were multipara, other authors reported PRAKI more common in multipara 62%,[ 11 ] 61.1%,[ 12 ] and 79.6%[ 13 ] respectively, while two studies reported PRAKI more common in primipara (52%). [ 14 15 ]…”
Section: Discussionmentioning
confidence: 53%
“…Other authors concluded, late referral from PHC was one of the reason of poor pregnancy outcome in their study. [ 10 12 ] One study reported that out of 40 patients with sepsis AKI, 34 (85%) were referred from primary care centres (PHC). [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…It is a serious obstetric complication associated with severe foetomaternal mortality and morbidity [3]. The incidence has declined due to improvements in reproductive health but it is still correlated with significant perinatal mortality and maternal morbidity [4]. It may be due to ischemic tubular necrosis or decline in renal perfusion from various conditions encountered during pregnancy [4].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence has declined due to improvements in reproductive health but it is still correlated with significant perinatal mortality and maternal morbidity [4]. It may be due to ischemic tubular necrosis or decline in renal perfusion from various conditions encountered during pregnancy [4]. Major PRAKI factors involving hypertensive conditions during pregnancy, sepsis, obstetric hemorrhage, acute fatty liver and thrombotic microangiopathy during pregnancy, [5] and freshly reported 10.55% incidence of postpartum AKI (PPAKI) along with sepsis and haemorrhage being the most common etiologies [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation